(untitled) (Pedagogy of Higher and Secondary Education, 2012)
Korolsky V. Integration of professional knowledge indicative - the basis of teacher training on the basics of technology predprinematelskoy activities. The article deals with the problem concerning one of the prior trends in Technology teacher training on the foundations of enterepreneurial activities. Presented and examined the structure and the content of the special course ‘‘Entepreneurial activities foundations’’ that is grounded on some profession-oriented knowledge in the process of a teacher training from the 1 st to the 4 th years of studies at the Faculty of Technology-and-Pedagogy and grounded on some knowledge of Financial Mathematics.